A Comparative Analysis of OpenVPN, WireGuard, and IKEv2/IPSec Using Ubuntu 24.04 LTS - Ahmad Tamim Ahmadi; Sebghatullah Aslamzai (Department of Informatics, Universitas Malikussaleh, 2026)
This paper presents a rigorous comparative analysis of three widely-used VPN protocols — OpenVPN, WireGuard, and IKEv2/IPSec — implemented and benchmarked on Ubuntu 24.04 LTS within a controlled VirtualBox virtualised environment on a Dell Inspiron 15 with 8 GB RAM. Each protocol was evaluated across throughput (iperf3, 30-second runs, 10 iterations), latency (ping, 100 packets), CPU utilisation, and packet jitter. Security was assessed via a structured feature matrix covering encryption, forward secrecy, authentication flexibility, formal verification, code complexity, and DPI resistance. WireGuard achieves the highest throughput (22.9 Mbps mean), lowest latency (4.7 ms), and minimal CPU footprint (9.8% server, 8.3% client). IKEv2/IPSec PSK delivers strong mid-range performance (16.8 Mbps, 8.2 ms). OpenVPN TCP/443 provides unique deep-packet-inspection evasion at a performance cost (8.7 Mbps, 14.3 ms). All three protocols provide AES-256-class encryption and perfect forward secrecy. Deployment scenario recommendations are provided for enterprise, performance-critical, and censorship-circumvention contexts.